ANALISIS FAKTOR YANG MEMPENGARUHI BRAND LOVE PADA GENERASI Z INDONESIA - Ali Wardhana; Tristano Aviel Sunara (Management Insight: Jurnal Ilmiah Manajemen, 2022)
Generational change is taking place in Indonesia where Generation Z has started to dominate and is enter the productive age which will certainly have an impact on Generation Z's perspective on a brand. Therefore, this study will try to understand more about brand love in Generation Z and the factors that will affect brand love by using Brand Experience and Brand Image. Sampling in this study was carried out using the purposive sampling method considering that the sample was addressed to a certain age group or generation Z. The sample data will be obtained through a questionnaire that is circulated online. The questionnaire items will use a Likert scale of 1 to 5 and will be tested and analyzed using a partial least square-structural equation modeling (PLS-SEM) approach. The results showed that brand experience and brand image have an effect on Brand Love where the impact caused by brand image is greater than the brand experience variable